PENGARUH KECERDASAN SPIRITUAL, GAYA KEPEMIMPINAN, DAN INSENTIF TERHADAP KINERJA PEGAWAI BANDARA MUTIARA PALU - Saida, Zainal (Katalogis, 2013)
The purpose of the research was: 1) to know and analyze simultaneous effects of spiritual quotient, leadership style and incentive toward the performance of Palu Mutiara Airport Officers ; 2) to know and analyze the effect of spiritual quotient toward the performance of Palu Mutiara Airport Officers; 3) to know and analyze the effect ofleadership style toward the performance of Palu Mutiara Airport Officers; 4 )to know and analyze the effect of incentive toward the performance of Palu Mutiara Airport Officers. The population of the research was the officers at Palu Mutiara Airport. Based on the data obtained from Sub Unit of Official Exertion that Palu Mutiara Airport Officer were 156 persons. From the calculation result of Slovin formula usage, the sample obtained was 60 persons with probability sampling technique which one of those is simple random where the names of the officers were randomized based on the working unit. Both primary and secondary data collection were through observation, interview, questionnaire and documentation. Multiple Linear Regression Analysis method used to examine the hypothesis of the research. The result showed that:1)Spiritual quotient, leadership style and incentive simultaneously effects positively and significantly toward the performance of Palu Mutiara Airport Officers;2) Spiritual quotient positively and significantly effect toward Palu Mutiara Airport Officers;3) Leadership style positively and significantly effect toward Palu Mutiara Airport Officers;4) Incentive positively and significantly effect toward Palu Mutiara Airport Officers.